Prevalence and Pattern of Hospital Acquired Infection in Surgery Ward, Dhaka City - Juma, Badrun Nahid; Alam, A S M Mahbub; Raida, Aantara; Pasha, Faisal Mohammed (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Hospital acquired infection among the patients of post-surgery is a global issue linked to extra burden on individual health, health sector and overall economy of the country. Prevention is the utmost important intervention to overcome this issue. Objective: To investigate the prevalence and pattern of Hospital acquired infection among the post-surgical patients in Dhaka city. Methods: This is the cross-sectional study conducted in Shaheed Suhrawardy Medical college hospital (Oral and Maxillofacial surgery ward) and Dhaka Medical college Hospital (General surgery and Gynae ward). The cross- sectional design observed 180 participants who undergo surgery and fulfilled specific inclusion criteria. Convenience sampling, a non-probability sampling technique, was used for participant selection. Data were collected by face-to-face history taking and considering history sheets with a semi- structured questionnaire. Results: Among 180 hospital admitted patients, a significant frequency of patients developed HAI 57.78% and in 42.22% did not develop HAI. The Male patients was 30% and female 70%. The Male patients who developed HAI were 8.89%, Female 48.89%. where 20% reported consuming smoked tobacco, 33.33% smokeless tobacco and 46.67% consumed no tobacco. So, a total of 53.33% of the population used tobacco. The study identified a significant association (p<0.05) between tobacco consumers and developing HAI. The maximum number of patients, 48.33% developed surgical wound infection, 6.11% developed catheter induced UTI, 1.67% developed bloodstream infection and 1.67% developed soft tissue infection. Amongst 180 patients, more than half 53.33% attended daily with an attendant. Only 40% attended with 2 attendants daily, and 6.67% with 3 attendants daily. 62.22% of patients had up to 2 visitors daily and 37.78% had above 2 visitors daily. The study identified a significant association p<0.05 between number of visitors per day and developing HAI. C/S reports were identified for 27.78% patients. The C/S test reports were not available for 72.22% patients at the time of data collection. The reports revealed a larger number 16.67% E.coli infection, 6.67% infected by Klebsiella and 4.44% were infected by Staphylococcus aureus. A significant increase in hospital stay was required in the case of patients who developed HAI (57.78%). Conclusion: This study revealed the prevalence of Hospital acquired infection significantly among post-surgical patients. There is an urgent need to solve the issue by securing targeted intervention. JAFMC Bangladesh, Vol 21, No 1 (June) 2025:52-55